Estado cognitivo y estrategias de compensación de memoria en personas adultas mayores - Domínguez Chávez, Claudia Jennifer (Horizonte Sanitario, 2021)
Aim: To explore the relationship between cognitive status and memory compensation strategies in older adults attending a daily activity center.Materials and methods: A descriptive and correlational design was applied in 110 older adults who attended a public recreational activities center. A personal data questionnaire, Montreal Cognitive Assessment, and Memory Compensation Strategies Questionnaire were applied. The research was conducted under the ethical current regulations for health research in Mexico.Results: 54.5% of participants had adequate cognitive status, 29.1% obtained scores indicative of probable dementia, and 16.4% of mild cognitive impairment. The most frequently used compensation strategy was time, followed by external, effort, internal, and reliance strategies. Cognitive status was related to the strategies of confidence (p= .002) and effort (p= .013). The mild cognitive impairment group used more time strategy (p= .026) compared to the other two groups. In contrast, the probable dementia group used more the reliance strategy (p= .013).Conclusions: The greater the cognitive decline, the greater the need to rely on another person, as well as the effort made to remember information. In addition, older adults with mild cognitive impairment spent more time to remember, while those with probable dementia compensated for the decline by relying on another person to remember. This knowledge could support in the future the development of interventions focused on compensating for cognitive impairment and thus help to delay cognitive decline.